Penilaian Pelayanan Transportasi Umum Surabaya Raya Dengan Metode Customer Statisfaction Index dan Importance Performance Analysis - Nur Indah Mukhoyyaroh; Prima Eko Agustyawan (Faculty of Engineering, Kadiri University, 2022)
Public transportation has a great potential in the transmission of Covid-19. For this reason, it is necessary to have good transportation services that can provide comfort and safety to users. Due to poor transportation services can cause users uncomfortable and unsafe. For this reason, it is necessary to assess the performance of transportation services. The purpose of this study is to assess the level of user satisfaction with public transportation services in the greater Surabaya area and to map sectors that need improvement. The research was conducted by giving questionnaires to users of public transportation in the Greater Surabaya area. From these data, instrument test was conducted. Furthermore, IPA analysis is carried out to obtain a mapping of the sectors that need to be improved. CSI analysis is also carried out to assess the level of user satisfaction with existing services. The results of this study obtained a value of 0.786 based on CSI analysis, which means that Surabaya land transportation users during the Covid-19 pandemic are satisfied. However, based on the results of the IPA analysis, it is necessary to increase the cleanliness of the transportation sector, lighting, and the application of PPE. Meanwhile, in the first aid kit sector, the availability of hand sanitizer and transportation stops is considered to have low importance, so that the authorities can focus on sectors that have high importance. The results of this study can be used as a reference in improving the quality of land transportation services.